1987
DOI: 10.2307/2046542
|View full text |Cite
|
Sign up to set email alerts
|

Weierstrass Weight and Degenerations

Abstract: ABSTRACT. It is shown that as a family of projective smooth curves degenerates to an irreducible Gorenstein curve the Weierstrass weight at a point P on the limit curve is the sum of the Weierstrass weights at points on the smooth curves converging to P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In contrast, singular points of irreducible curves, at least those with Gorenstein singularities, are always limits of Weierstrass points. Major work was done by Widland, Lax and Garcia ( [18], [31], [32], [33], [41]) in the 1980's and early 1990's to define and study Weierstrass points of linear systems on such curves. In particular, Lax showed that these Weierstrass points are the limits of the Weierstrass points of linear systems on smooth curves degenerating to the given linear system on the singular curve; see [32], Prop.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, singular points of irreducible curves, at least those with Gorenstein singularities, are always limits of Weierstrass points. Major work was done by Widland, Lax and Garcia ( [18], [31], [32], [33], [41]) in the 1980's and early 1990's to define and study Weierstrass points of linear systems on such curves. In particular, Lax showed that these Weierstrass points are the limits of the Weierstrass points of linear systems on smooth curves degenerating to the given linear system on the singular curve; see [32], Prop.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we are able to consider families of singular curves in any characteristic, instead of a single curve as in the previous literature (see however [13] in characteristic 0). In [10] Laksov and Thorup independently introduce substitutes for the sheaves of principal parts on an integral, Gorenstein curve.…”
Section: Introductionmentioning
confidence: 99%
“…Weierstrass points on integral Gorenstein curves were defined in [13] using the (canonical) line bundle of dualizing differentials. The limit Weierstrass points on such a fiber in a family are these intrinsically defined Weierstrass points by [9]. Put…”
mentioning
confidence: 99%